Francesco Crispi, 1818-1901 from nation to nationalism - Duggan, Christopher (Oxford University Press, 2002)
Francesco Crispi was one of the architects of Italy's unification. From revolutionary democrat to authoritarian, he was feted by the fascist regime as the precursor to Mussolini. This text aims to shed light on the roots of fascism.